Scrooge & Marley [videorecording (DVD)] - Knight, Richard, Jr; Stoneking, Ellen; Imse, Timothy; Pevsner, David; Kazurinsky, Tim; Schwimmer, Rusty; Vilanch, Bruce (Darkstar Pictures, 2022)
It is a modern day, queer variation on Charles Dickens's classic story of the holidays, A Christmas Carol. On Christmas Eve, Ben Scrooge, the man who hates the holidays, is given the chance to begin again when he is visited by three spirits, the Ghosts of Christmas Past, Present, and Future. Revisiting the tragic missteps of his life enables Scrooge to rediscover the joy of the holiday season and make a journey back to love. Recounted from a gay sensibility with heart, comedy, and music, the magic of Dickens' timeless tale comes alive from a fresh perspective that will appeal to audiences of all persuasions.